Usia Kawin Perempuan dalam Paradigma Hukum Islam - Nur Anissa; Arfin Hamid; Ratnawati Ratnawati (DOKTRINA: JOURNAL OF LAW, 2021)
Islamic law does not determine the age of marriage for women, but only provides the conditions according to the Surah An-Nur Verse (6) and (32), Marriage may be carried out if it is old enough or fit for marriage or maturity". The Islamic Law Compilation (KHI) determines the age of marriage if it reaches the age of 16 years, this is subject to debate because national law determines the age of 16 years is the age of children or minors who still need education or physical and mental maturity. This study aims to analyze the paradigm of Islamic law on the age of marriage for women, the normative aspects of female marriage at an early age and the implementation of early marriage for women. This study uses a normative approach, namely examining existing problems normatively and factually using applicable laws and regulations and legal theories supported by literature data studies, research is carried out by examining library materials to obtain secondary data. The scholars agree that women can marry if they have adults with characteristics, namely: First, physically able (physically) marked by menstruation usually occurs at the age of 9 to 17 years. The second requirement is being able to be psychologically related to the education or way of thinking of a woman to deal with various conditions in marriage. The factor of a woman's maturity varies in each region because it is influenced by culture, women's physicality (reproduction), education and so on. In this era of globalization, with the factors mentioned above, it is ideal for women to marry when they are 21 years old.